Brand Pyramid: Toolkit for better Mileage - Jyothsna Priyadarsini, K.; Goodwin, D. R. (SFIMAR Research Review, 2010)
The eternal buzzword used by marketers is "Brand". With milestone advancing in the global market places and escalating brands in the global, many companies think and rethink their tried-and-true branding strategies. An increasing number of 21st century marketers are seeking avant-garde ways to build and strengthen brand equity in a highly competitive environment. Brand managers are envisaging a shrink in the brand loyalty and brand equity. They are reveriting the old rules with a better approach. They are studying the models of brand building to enrich their branding strategies for a better mileage. The paper titled "Brand pyramid: Toolkit for better mileage" raises the curtain with a Brand pyramid model developed by Keller. The rationale of the brand equity pyramid is to outline the basic building blocks of what the brand should stand for in order to guide the process of building brand equity. It is the basis for determining key elements of the brand strategy - brand vision, brand positioning, and brand personality and brand measurement. Brand building pyramid is a framework of strategic brand management. The paper unravel the various aspects covered by keller’s brand building pyramid that includes Brand salience, brand performance and imagery, brand judgment and feelings and brand resonance. The paper chips examples of Indian context that align with the blocks of the pyramid. A/so, the paper unravels the other eminent models of brand building. The paper concludes with the theme of the Keller’s model as "The length of time to build a strong brand will therefore be directly proportional to the amount of time it takes to create sufficient awareness and understanding so that firmly held and felt beliefs and attitudes about the brand are formed that can serve as the foundation for brand equity".